Membrane computing 11th International Conference, CMC 2010, Jena, Germany, August 24-27, 2010. Revised Selected Papers - Gheorghe, Marian; Hinze, Thomas; Paun, Gheorghe; Rozenberg, Grzegorz; Salomaa, Arto (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 11th International Conference on Membrane Computing, CMC11, held in Jena, Germany, in August 2010 - continuing the fruitful tradition of 10 previous editions of the International Workshop on Membrane Computing (WMC). The 23 revised full papers presented together with 4 invited papers and the abstracts of 2 keynote lectures were carefully reviewed and selected from numerous submissions. The papers address in this volume cover all the main directions of research in membrane computing, ranging from theoretical topics in the mathematics and computer science to application issues. A special attention was paid to the interaction of membrane computing with biology and computer science, focusing both on the biological roots of membrane computing, on applications of membrane computing in biology and medicine, and on possible electronically based and bioinspired implementations.